Pengaruh Aromaterapi Lemon terhadap Emesis Gravidarum Trimester I - Aida Fitria; Ade Ayu Prawita; Sari Yana (Poltekkes Kemenkes Palu, 2021)
Introduction: Emesis gravidarum or nausea, vomiting, which often occurs in the first trimester of pregnancy, if left untreated, will cause problems for pregnant women and the fetus. Handling of emesis gravidarum can be done with pharmacological and non-pharmacological treatments such as lemon aromatherapy. According to Riskesdas Jambi province in 2018, complications experienced by pregnant women amounted to 14.36% of them experienced nausea and vomiting. Objective: To determine the effect of lemon aromatherapy on emesis gravidarum in pregnant women in the first trimester at the Rosita Village Midwife Clinic, Pasar Monday, Jambi Province in 2020. Method: The research was pre-experimental design approach in the form of one group pre-test and post-test. The study population was 20 people. The sample were taken by using a purposive sampling technique amounted to 15 respondents, the statistical test used was the depnden t test. Result: The data obtained the pre-test mean of 10,20 and SD of 1.486, while the post-test of mean of 4,80 SD of 1.234. From the results of the statistical test, namely the paired t-test with a confidence level of 95%, it is known that the p-value=0.000. Conclusion: There is frequency reduction in first trimester emesis gravidarum by giving lemon aromatherapy Lemon Aromatherapy in Trimester I Pregnant Women.